Factors contributing entrepreneurial intention among UMK students - Tan, Xing Jie; Nordin, Nor Afifah; Abdullah, Nurul Syuhaida; Mukhtar, Siti Zuhaili (2015)
Entrepreneurial development today has become very significant and crucial, that in the view of its being a key to economic development. The objectives of industrial development, regional growth and employment generation depend upon entrepreneurial development. Furthermore, entrepreneurship is a key driver of our economy. Wealth and a high majority of jobs are created by small businesses started by entrepreneurially minded individuals, many of whom go on to create big businesses. People exposed to entrepreneurship frequently express that they have more opportunity to exercise creative freedoms, higher self-esteem and an overall greater sense of control over their own lives. There were some issues addressed that the factors contributing entrepreneurial intention among UMK students and it mainly focused on entrepreneurial traits, entrepreneurial competencies, family background and supporting environment, Therefore, the problem to be addressed by this study was the problems that influence the students’ intention to become entrepreneur as career choice. The study is focus on the factors that contribute entrepreneurial intention among UMK students. The variables involved in the study were the entrepreneurial traits, entrepreneurial competencies, family background and supporting environment. This study was applied quantitative approach by distributed self-administered questionnaires to the 346 UMK undergraduate students from Faculty of Entrepreneurship and Business (FKP), City Campus, University Malaysia Kelantan, Pengkalan Chepa, Kelantan. The results showed that the three variables which are entrepreneurial traits, entrepreneurial competencies, family background and supporting environment have strong relationship in contributing entrepreneurial intention among UMK students. The study wasto expose and clarify which factors were more influential in affected the students; career choice. Generally, this finding would bring clear thinking to UMK undergraduate students to plan their future career as entrepreneur.